The Effect Of Jicama Flour Subtitution On The Quality Of Cat’s Tongue Cookies - Lestari, Dian; Gusnita, Wiwik; Holinesti, Rahmi; Insan, Ranggi Rahimul (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research is motivated by Cookies are small foods with a dense and crunchy texture that are made by baking or in the oven and last more than one month (Rahma Wati, 2013:26). There are various types of cookies in Indonesia, one of which is cat’s tongue cookies. Cat tongue cookies come from the Netherlands, in dutch these cookies are usually called “KATTE TONG”. Therefore, in this research the author used jicama flour as a partial substitute for wheat flour in making cat’s tongue cookies. This research aims to analyze the effect of 15%, 30%, 45% substitution of jicama flour on the quality of the shape, color, aroma, texture, and taste of the cat’s tongue cookies produced. This type of research is a pure  ecperiment (true experiment) with a completely randomized design method with one factor. The type of data is primary data sourced from 3 expert panelists who filled in the organoleptic test format. The data obtained was tabulated in table form and analysis of variance (ANOVA) was carried out, if it was significantly different, it was continued with the Duncan test.